2005
DOI: 10.1002/ar.b.20068
|View full text |Cite
|
Sign up to set email alerts
|

Origin of corpses received by the anatomical institute at the University of Jena during the Nazi regime

Abstract: During the Nazi regime (1933-1945), the anatomical institute at the University of Jena received 2,224 corpses, of which approximately 200 originated from executions. The available data clearly suggest that a large portion of these 200 executed persons must be considered victims of Nazi crimes. Approximately an equal number of bodies were delivered from state nursing homes and mental institutions in the state of Thuringia during the same time period. The available data suggest that it is highly likely that many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 4 publications
0
19
0
3
Order By: Relevance
“…German and Austrian anatomists benefited from these changes through an unprecedented cadaver supply mainly used for teaching purposes, but also for research [52,[54][55][56]. By making use of the cadavers, they, willingly or not, colluded with a political strategy that sought to eliminate not just dissidence, but also eliminated the very memory of the dissidence, in so far as the executed were denied proper burial [35].…”
Section: Discussionmentioning
confidence: 99%
“…German and Austrian anatomists benefited from these changes through an unprecedented cadaver supply mainly used for teaching purposes, but also for research [52,[54][55][56]. By making use of the cadavers, they, willingly or not, colluded with a political strategy that sought to eliminate not just dissidence, but also eliminated the very memory of the dissidence, in so far as the executed were denied proper burial [35].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the bodies of executed persons was a general practice in the German Anatomical Institutes during the NS regime (Aumueller and Grundmann, 2002;Redies et al, 2005), and was openly recorded in publications from this time period. For example, in research by the above-mentioned Pernkopf pupil, Heinrich von Hayek, who reported the use of lungs from executed persons and 5 gesunde Tonsillen von Hingerichteten (five healthy tonsils from executed persons) for his studies (Hayek 1941(Hayek , 1942.…”
Section: Results From the Senatorial Project Of The University Of Viennamentioning
confidence: 99%
“…Several new historical analyses of German anatomical institutes, e.g., in Marburg and Jena, have been published recently and refer to the Pernkopf discussion and the Viennese investigations (Aumueller and Grundmann, 2002;Redies et al, 2005).…”
Section: Impact On the Historical And Ethical Debatementioning
confidence: 99%
“…The only recorded refusals give as reason that cadaver storage capacities were exhausted (Redies et al, 2005). In contrast, only occasional reference to research on executed criminals can be found in the US literature of the time (Jones, 1941) while British anatomists even openly envied their German colleagues for their access to ''such valuable sources of material'' (Lewinsky and Stewart, 1936).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently attention has turned to those researchers who were not outright murderers or criminals but nevertheless supported the Nazi system in various ways (Editorial, 2005). We hope to make a more nuanced contribution to the historical study of anatomy during Nazi times, which so far consists of local studies for Bonn (Forsbach, 2006), Jena (Redies et al, 2005), Marburg (Aumüller and Grundmann, 2002), Tübingen (Mörike, 1988;Schön-hagen, 1992), and Vienna (Malina and Spann, 1999;Angetter, 2000;Hubenstorf, 2000), of which only the latter study, concerning the anatomist Pernkopf and his anatomical atlas, has attracted widespread international attention.…”
Section: Introductionmentioning
confidence: 99%